Measuring the Implementation of a School Wellness Policy. (October 2017) - Snelling, Anastasia; Belson, Sarah Irvine; Watts, Erin; Malloy, Elizabeth; Van Dyke, Hugo; George, Stephanie; Schlicker, Sandra; Katz, Nancy Brenowitz
ABSTRACT: BACKGROUND: With the rise in childhood obesity, school policies related to nutrition and physical activity have been written and implemented. In this paper, we present a model to evaluate the degree to which state legislation for school health policies are implemented at the school level. METHODS: Using Washington, DC's Healthy Schools Act (HSA) and a self‐report measure of the implementation of the HSA, we illustrate the process of developing a composite score that can be used to measure compliance with the provisions of the law. RESULTS: We calculated elementary and middle school composite scores based on the provisions within the HSA. Schools have been successful in implementing nutrition provisions; however, more resources are needed for schools to achieve the minutes of health and physical education. We found statistically significant differences between public charter and traditional public schools on the implementation of the provisions of the HSA. CONCLUSIONS: Understanding how schools are complying with school wellness policies is a next step to determining where additional resources or support are needed in order to support school‐wide adoption of healthy policies.